Fractal Complexity in Spontaneous EEG Metastable-State Transitions: New Vistas on Integrated Neural Dynamics - Allegrini, Paolo; Paradisi, Paolo; Menicucci, Danilo; Gemignani, Angelo (Frontiers in Physiology, 2010)
Resting-state EEG signals undergo Rapid Transition Processes (RTPs) that glue otherwise stationary epochs. We study the fractal properties of RTPs in space and time, supporting the hypothesis that the brain works at a critical state. We discuss how the global intermittent dynamics of collective excitations is linked to mentation, namely non-constrained non-task-oriented mental activity.